The Effect of the Graphic Organizer Method on Students’ Ability to Write Recount Text at Grade X - Rahma Yunita Ansi; Dian Anggraini Harahap; Datulina Ginting; Karimaliana Karimaliana; Ali Hasimi Pane (research, training and philanthropy institution Natural Aceh, 2023)
This research concerns the students' ability in writing recount text. The problem of the study was: Teachers still used conventional methods in every meeting, causing boredom among the students. Students had less vocabulary, and Students did not master grammar. Students were unable to express their ideas. This research used a non-experimental research design. The data were collected by using the test. To obtain the data, the grade X of MAS Muhammadiyah 2 Kisaran is selected as the respondent. The research subject was grade X MIPA 1 and X MIPA 2. Each class consists of 30 students. The total number of students was 60 students. The reason for choosing this class was because the writer found some students' problems in writing recount text. After the data were analyzed, it could be concluded that there was an effect of the graphic organizer method on the student's ability to write recount text at grade X of MAS Muhammadiyah 2 Kisaran in the 2021/2022 Academic Year. It was proven that there was a high correlation between using the clustering technique and the student's ability to write recount text tcount > ttable. With the description tcount = 7.49 while the ttable = 2.002 (5%).and their relevance in formal evidence to solve real problems.